Acardius Amorphus: Magnetic Resonance Imaging (MRI) can be helpful in the Diagnosis when Ultrasound (US) is Inconclusive - Abd. Aziz, Azian; R, Anna Liza (Malaysian Medical Associations, 2011)
An acardiac twin is rare and the diagnosis is commonly achieved from antenatal ultrasound (US) scans. However there have been cases where the appearances of the acardiac twin can be confusing and mimics a mass or tumour, for example, a teratoma. We experienced a case where the findings were unclear from the antenatal ultrasound scans and we had to resort to Magnetic Resonance Imaging (MRI), where we finally made the correct diagnosis based on the identification of two umbilical cords, supplying the normal fetus and the ‘mass’ (acardiac twin)respectively.